Tannbehandlingsangst blant den samiske befolkningen i Finnmark. En del av Tannhelse i Nord-prosjektet - Partapuoli, Ul-Juhan; Tellefsen, Ole Mahtte Eira (UiT Norges arktiske universitet, 2017)
Abstract Introduction: There is a lack of knowledge regarding dental anxiety among indigenous people and therefore, it is important to learn more about this condition. Dental anxiety can be a challenge for both patients and clinicians. The aim was to investigate if there were any differences in dental anxiety between people of Sámi and Norwegian origin. Materials and methods: 2,493 individuals, residing in five municipalities in Finnmark County, were invited to the study, which consisted of a free-of-charge clinical examination and a questionnaire. The questionnaire consisted of demographic questions and the Dental Anxiety Scale (DAS). In total 2,118 individuals (57 percent women) approved to participate. Of those were 1,298 (63 percent) of Sámi origin. Total DAS-sum was used as dependent variable and Pearson’s Chi2-test, Independent Samples T-test and One-way ANOVA were used to investigate differences between groups. Result: There were no difference in dental anxiety between Sámi and Norwegian participants. The younger age group showed a greater degree of anxiety compared to the older age group (p<0.001). Similarly, female participants showed higher level of anxiety (p<0.001) compared to men. Conclusion: This study showed no difference in dental anxiety between a Sámi and Norwegian population. Females compared to men, expressed a higher level of dental anxiety in both of the populations.